On the Benefits of Cumulative Exams: An Experimental Study. - Kiger, Jack E. (The Accounting Review, 1984)
Abstract ABSTRACT: This study analyzes the effect of two review strategies on performance, effort, and attitude measures. The two review strategies are compared with a control strategy that does not include a review treatment. The review treatments are administered through two separate testing procedures. One procedure includes individualized review questions on each succeeding examination. The other includes randomized review questions on succeeding exams. The results indicate that reviews are a cost-effective means of improving student performance. The random review treatment proved to be the more efficient strategy. Further, the data implied that students were unable to assess properly the benefits of reviews. This finding suggests that instructors should take the initiative to employ strategies that force students to review on a regular basis.